ETHNOBOTANICAL, PHYTOCHEMICAL AND PHARMCEUTICAL STUDIES OF MEDICINAL PLANT, VENTILAGO MADERASPATANA GAERTN (RED CREEPER): A REVIEW - Periyasamy, Karuppannan; Kaliyaperumal, Saravanan (International Journal of Current Pharmaceutical Research, 2016)
Traditional plant therapies increasing in recent decade has a new wave of the research interest in plant kingdom. Scientific studies on a number of medicinal plants indicate that promising phytochemical compounds can be developed new drugs for many health problems. Ventilago maderaspatana (Red creeper) is medicinal plant traditionally used for the control of various diseases such as dyspepsia, leprosy, puruitis, etc. Chemical studies have shown that, stem bark contains Flavonoids, tannins etc. Some parts of its phytochemicals possess anticancer, antidiabetics and antiulcers activities. Thus, the present review made an attempt to highlight the ethno botanical and traditional uses as well as phytochemical and pharmacological studies on V. maderaspatana and it will help to develop new ailments for the treatment of various diseases.